Recycling household waste as a solution to the scarcity of subsidized fertilizer in Jetis Hamlet - Minar Ferichani; Darsono Darsono; Sri Marwanti; Wiwit Rahayu; Umi Barokah; Ernoiz Antriyandarti (Community Empowerment, 2023)
Jetis Hamlet, Karanganyar Regency, is currently facing two urgent problems simultaneously: river pollution and fertilizer scarcity. The aim of the RG-EPP community service is to provide education on processing household waste into liquid organic fertilizer (LOF). Methods employed to achieve this goal include socialization, counseling, technical direction, creating video tutorials, training, practicing LOF-making skills, and conducting LOF laboratory tests. The results of this community service activity, besides addressing the issues of river pollution and fertilizer scarcity, indicate that the community has acquired knowledge and skills to produce high-quality liquid organic fertilizer. This fertilizer can be applied in rice farming using household waste as a raw material.